A comparative study of geosynthetically reinforced earth foundations in multi-utility transportation infrastructure for high-speed railways - Mandhaniya, Pranjal; Soni, Anish Kumar; Choudhary, Kirti; Ansari, Abdullah (Frontiers in Built Environment, 2023)
A high-quality railway track resting on an excellent foundation is required to support high-speed railway transportation. The foundations of high-speed railway tracks are generally constructed on the lifted embankment with the improved ground using different reinforcement agents like geosynthetics and rigid lateral support. The present study performed dynamic finite element simulations on a ballasted rail track laid over a geosynthetically reinforced embankment with and without facing wall support. Three foundation geometries were analyzed to examine the effect of facing wall support and geosynthetics on the lateral resistance of the foundation. An area loaded with a constant pressure was moved at a constant speed, causing the load motion at different speeds in the 90–360 km/h range. Different parameters were calculated at node paths to help understand the lateral effect of moving load. The results showed that the lateral resistance based on nodal acceleration and velocity increased with facing wall support in the range of 40%–57%. Any increment over the minimum facing wall thickness of 300 mm does not significantly increase lateral resistance. Geosynthetics provided a vital function in the foundations with a less bulk volume of soil and increased the lateral resistance by 10%.